Cold steam - Yang, Sishuo (2015)
Cold Steam is a visual effects (VFX) short film produced by Nicholas Chia, Yeo Shiyun, Goh Peng Fong, and myself. Based in a post-apocalyptic world, Cold Steam is the story of a girl’s struggle for water in a world infested by mysterious creatures. Approach The project aims to primarily examine and undergo the visual effects pipeline, as well as the technical exploration of 3D production and compositing software such as Maya, Mudbox, ZBrush, Realflow, and Nuke. In addition, the filming aspect was also a huge part of the project, and was shot in front of a green screen in ADM’s soundstage with an ALEXA camera. Originality/Value As the pioneer batch of visual effects students in ADM, Cold Steam is one of the first ever VFX final year projects in ADM, and also one of the few examples of a multi-disciplinary collaboration across different majors.